EXPLORING BPJS KETENAGAKERJAAN MEMBERS’ SATISFACTION ON THE UTILISATION OF TECHNOLOGY OF JMO - Rizky Fajar Setiawan; I Nyoman Rasmen Adi (SEAN Institute, 2023)
This study aimed at exploring the members of BPJS Ketenagakerjaan in Banuspa Regional Area satisfaction on the the use of the JMO application, (b) exploring user perceptions of the application and services of the BPJS Ketenagakerjaan in Banuspa area through JMO in providing services, and (c) developing a strategy for optimizing the use of JMO in BPJS Ketenagakerjaan in the Banuspa Regional Office work area. That was mixed-method research in which used both qualitative dan quantitative data. The results of analysis showed that the members were satisfied on the use of JMO application. The members were also providing positive response on the services provided by BPJS Ketenagakerjaan in the Banuspa Regional Area. To optimize the JMO application, BPJS Ketenagakerjaan in Banuspa Regional Area needs to spreading the information about the application to wider community.